THE EFFECTS OF MIXTURES OF VARIOUS CONCENTRATIONS OF CARBOXYMETHYL CHITOSAN/AMORPHOUS CALCIUM PHOSPHATE WITH GYPSUM ON DENTIN REMINERALIZATION - MAHARTI, IKE DWI; SUPRASTIWI, ENDANG; SETIATI, HASTI DWI; YAMIN, ERLIYANA; CAHYANI, ANDI NURWALINI (International Journal of Applied Pharmaceutics, 2020)
Objective: Carboxymethyl chitosan/amorphous calcium phosphate (CMC/ACP) is a non-collagen protein analog with the ability of dentin remineralization, and gypsum is a compound material than can facilitate application of CMC/ACP. CMC/ACP concentration is claimed to increase calcium and phosphate concentration, which indicates dentin remineralization. The aim of this study is to observe the effects of different concentrations of CMC/ACP mixed with gypsum on dentin remineralization. Methods: Occlusal cavities were created in 18 freshly extracted teeth, and the teeth were divided into three groups. The first group consisted of untreated demineralized dentin, and the second and third groups were treated with mixtures of 2.5% and 5% CMC/ACP and gypsum. All groups were checked and analyzed on the 14th day using scanning electron microscopy/energy-dispersive X-ray spectroscopy and one-way ANOVA (p<0.05). Results: Significant differences (p=0.001) of calcium and phosphate concentrations were found between Groups I, II, and III (p=0.001), whereas no differences were found between Groups II and III. Conclusion: Gypsum and CMC/ACP work synergistically to induce dentin remineralization. The highest dentin remineralization was shown by 5% CMC/ACP-gypsum mixture, but the level was not statistically different from that of 2.5% CMC/ACP-gypsum mixture.